THE EVALUATION OF PROVINCIAL SPORT TRAINING CENTER (PELATDA) TOWARDS NATIONAL SPORT COMPETION (PON) XIX/2016 WEST JAVA - Palmizal A (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
AbstractThe purpose of this study is to evaluate theprogramof Jambi training centre to Jawa Barat. This research usesquantitative and qualitative approaches,evaluation methods using model Context, Input, Process, and Product (CIPP) developed by Daniel L. Stufflebeam.The data were collected by m means oftriangulation method, using questionnaires, interviews, observation and document study.The results show that: (1) The evaluation context: it has alegal basis and a strong enough Government;goals and policies are well executed; but the responses in accordance with the athletes are so poor. (2) The evaluationInput; the stages of planning the structure exercise program of goes well. But selection process for athletes, coaches, manager still needs to be improved. Thefinancial and infrastructure supports need to be restructured and improved according to the needs of PELATDA Jambi.(3) The evaluation Process; the trainer’s exercise program has met the athlete’s needs.The planning and assessment during exercise still needs to be improved.The implementation of the championship of PON XIX Jawa Barat in 2016 have seemed to run well and this is in line with the results of evaluation and monitoring, showing that all have gone well and very good.(4) The evaluation of the Product; the increasing physical fitness with qualified and professional athletes and results of PON XIX Jawa Barat in 2016, the Jambi team athletes achieved an excellent result, exceedingthe targets with6 gold, 6 silver, and 21 bronze medals.But for the athlete’s performance must have to be increasedand have not been able to contribute to Jambi training centre; this is an evaluation for the implementation of the next Jambi training centre and for obtaining better performance and achievement in the next championship.Keyword: The Program Evaluation, Training Centre